Technetium-99m labelled liposomes to image experimental arthritis. Issue 6 (1st June 1997) - Boerman, Otto C; Oyen, Wim J G; Storm, Gert; Corvo, M Luisa; van Bloois, Louis; van der Meer, Jos W M; Corstens, Frans H M
Abstract : OBJECTIVES: Liposomes sterically stabilised with polyethylene glycol (PEG) labelled with technetium-99m were tested for their ability to image adjuvant arthritis in a rat model. METHODS: Adjuvant arthritis was induced in the ankle joint of the left hind foot by injection of Mycobacterium butyricum in Freund's incomplete adjuvant in the foot pad. Seven days later animals received the following radiopharmaceuticals labelled with 99m Tc (a) non-PEG-liposomes, (b) PEG-liposomes or (c) non-specific human polyclonal IgG. For each of the radiopharmaceuticals the in vivo distribution of the radiolabel was monitored both scintigraphically as well as by counting the dissected tissues at two, eight, and 24 hours after injection. RESULTS: The pharmacokinetics of the radiopharmaceuticals differed considerably (half life in the blood: PEG-liposomes (18 hours) > 99m Tc-IgG (3 hours) > non-PEG liposomes (1 hour)). The inflamed focus was visualised with each of the agents. The uptake of each of the radiopharmaceuticals in the inflamed ankle region correlated with their residence time in the blood (inflamed joint uptake: PEG liposomes (1.15% injected dose (ID)/g)> 99m Tc-IgG (0.35% ID/g)>non-PEG-liposomes (0.05% ID/g)). Quantitative analysis of the images showed that the inflamed ankle to background ratio was highest with the PEG-liposomes (7.5 at 24 hours after injection), while with the other two agents this ratio did not exceed 4. CONCLUSION: This study shows that 99m Tc-labelled PEG-liposomes may be an excellent agent to visualise arthritis. Increased label uptake in the inflamed joint and increased target to background ratios can be obtained with PEG-liposomes because of their long circulating properties. In addition to their use as vehicles for scintigraphic imaging of arthritis PEG-liposomes might also be used for the site specific delivery of antirheumatic drugs.